Apostle's Cove : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2025)
"A few nights before Halloween, as Cork O'Connor gloomily ruminates on his upcoming sixtieth birthday, he receives a call from his son, Stephen, who is working for a nonprofit dedicated to securing freedom for unjustly incarcerated inmates. Stephen tells his father that twenty years ago, as the newly elected sheriff of Tamarack County, Cork was responsible for sending an Ojibwe man named Axel Boshey to prison for a brutal murder that Stephen is certain he did not commit. Cork feels compelled to reinvestigate the crime, but that is easier said than done. Not only is it a closed case but Axel Boshey is, inexplicably, refusing to help. The deeper Cork digs, the clearer it becomes that there are those in Tamarack County who are willing once again to commit murder to keep him from finding the truth. At the same time, Cork's seven-year-old grandson has his own theory about the investigation: the Windigo, that mythic cannibal ogre, has come to Tamarack County...and it won't leave until it has sated its hunger for human blood"--